CATATAN NIKAH MENURUT PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Muhammad Iqbal (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2011)
Marriage has a vital value in personal life, family and social life. The act No.1, 1974 about marriage and its various directions for use, requires all citizen to register their marriage at a legal institution (The office of religious affair) in order to have legal force. However, Islamic law does not require the registration of marriage because, in Islamic law it is more important to fulfill the obligatory rules of marriage it self. The discussion in this writing aims to explore the position of marriage registration in Islamic Law Perspective and Positive Law in Indonesia. Key words: marriage registration, legal force women                     and children protection.